Nurses’ attitude towards patient advocacy and its associated factor in East Gojjam Zone Public hospitals, Northwest Ethiopia, 2023 - Abay Tadie; Mikiyas Muche; Tiliksew Liknaw; Afework Edmealem (BMC Nursing, 2024)
Abstract Introduction One of the most important but underappreciated roles of nurses is patient advocacy. To advocate for patients effectively, the nurses should have a favorable attitude towards patient advocacy. Despite this fact, the nurses’ attitude towards patient advocacy was not known in Ethiopia. Thus, this study aimed to assess nurses’ attitude towards patient advocacy and its associated factors in East Gojjam Zone Public Hospitals, Northwest in 2023. Methods Institutional-based cross-sectional study design was conducted among 385 nurses in East Gojjam Zone Public Hospitals from March 1 to April 30, 2023. Nurses were selected using simple random sampling techniques from 11 public hospitals. The data were collected in a self-administered way. Binary logistic regression was used for data analysis. All independent variables having a P value of < 0.25 in the bivariable logistic regression were fitted into a multivariable logistic regression. The AOR at a 95% confidence interval was used to identify the strength of the association, and a p value of 0.05 was used to declare it statistically significant at the final model. Result A total of 385 nurses participated in the study, for a 91% response rate. Among these, 49.9% of nurses had an unfavorable attitude. Being working in a primary hospital [AOR = 2.3; 95% CI: (1.4–3.8)], poor cooperation of nurses [AOR = 1.7; 95% CI: (1.1–2.8)], being unsatisfied with the job [AOR = 1.7; 95% CI: (1.1–2.7)], and poor perceived supervision of work [AOR = 6.2; 95% CI: (3.7–9.8)] were factors associated with nurses’ attitudes towards patient advocacy. Conclusion The number of nurses who had an unfavorable attitude towards patient advocacy was high. Working in a primary hospital, poor cooperation with others, being dissatisfied with the job, and having an unfavorable perception towards the supervision of work were the factors associated with the unfavorable attitude of nurses towards patient advocacy. It is recommended that all hospitals better support the nurses to increase their job satisfaction and have good supervision of the nurses’ activities.